A Hegemonic View on Short Story Aku dan Mereka Berbeda - Evie Shofiyah Usman (Journal of English Language Teaching and Cultural Studies, 2020)
This study aims to determine the form of hegemony of the employer's power against the servants on short story Aku dan Mereka Berbeda. The Post-colonialism analysis was used to obtain in-depth understanding and information about the form of hegemony of the employer’s power conveyed by story. Source of data were taken from the short story entitled Aku dan Mereka Berbeda written by Abdul Latief. The short story itself was contained on a short stories collection Melihat tanpa Mata published by Gong Publishing in 2010. Based on the results of the research, it can be concluded three main characters that play a role in Abdul Latief's short story as figures reflected on colonialism. The employer figure is shown as a colonial nation, a servant figure as a colonized nation, and the author figure as a freedom fighter. The short story also conveys an ideological hegemony of white skin supremacy. The hegemonic aspect of power is also evident in this short story with the depiction of employers as the upper class and the servant as the lower class. The gender hegemony can also be seen in this short story through the depiction of women as lowly and oppressed domestic servant.